Impact of photodynamic diagnosis-assisted transurethral resection of bladder tumors on the prognostic outcome after radical cystectomy: results from PROMETRICS 2011 - May, Matthias; Nuhn, Philipp; Hohenfellner, Markus (World journal of urology, 2017)
PurposeResults of a retrospective single-institution study recently suggested improved prognostic outcomes in patients undergoing photodynamic diagnosis (PDD)-assisted transurethral resection of bladder tumor (TURBT) prior to radical cystectomy (RC). We sought to validate the prognostic influence of PDD-assisted TURBT on survival after RC by relying on a multi-institutional dataset.MethodsTo provide a homogeneous study population, patients with organ metastasis at the time of RC and/or after neoadjuvant chemotherapy were excluded from analysis, which resulted in overall 549 bladder cancer (BC) patients from 18 centers of the Prospective Multicenter Radical Cystectomy Series 2011 (PROMETRICS 2011). To evaluate the influence of PDD conducted during primary or final TURBT on cancer-specific mortality (CSM) and overall mortality (OM) after RC, bootstrap-corrected multivariate Cox proportional-hazards regression models were applied (median follow-up: 25 months; IQR: 19-30). Sensitivity analyses were performed for both patients with pure urothelial carcinoma and patients undergoing one single TURBT only.ResultsIn 88 (16.0 %) and 100 (18.2 %) patients, PDD was used in primary and final TURBTs, respectively. In 335 (61.0 %) patients, a single TURBT was performed prior to RC; in 194 patients (35.3 %), TURBT had been performed in a different center. CSM and OM rates at 3 years were 32 and 40 %, respectively. Use of PDD during primary or final TURBT was no independent predictor of CSM or OM. These results were internally valid and were confirmed in sensitivity analyses.ConclusionsPDD utilization during TURBT prior to RC does not independently impact the prognosis of BC patients after RC.